2020 11th International Conference on Computing, Communication and Networking Technologies (ICCCNT) 2020
DOI: 10.1109/icccnt49239.2020.9225621
|View full text |Cite
|
Sign up to set email alerts
|

Using Exploratory Data Analysis for Generating Inferences on the Correlation of COVID-19 cases

Abstract: Exploratory Data Analysis (EDA) is a field of data analysis used to visually represent the knowledge embedded deep in the given data set. The technique is widely used to generate inferences from a given data set. Data set of current pandemic, the COVID-19 is widely made available by the standard dataset repository. EDA can be applied to these standard dataset to generate inferences. In this paper, data visualization technique is applied to the dataset and is used to formulate patterns for better insights on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The concept of Exploratory Data Analysis (EDA) has been applied by Joanita and Senthil Velan [5] on developing correlation among the COVID-19 cases. Based on the statistical analysis it was found that there exists higher correlation between the identified characteristics of the COVID-19 patients in the countries of study.…”
Section: Existing Workmentioning
confidence: 99%
“…The concept of Exploratory Data Analysis (EDA) has been applied by Joanita and Senthil Velan [5] on developing correlation among the COVID-19 cases. Based on the statistical analysis it was found that there exists higher correlation between the identified characteristics of the COVID-19 patients in the countries of study.…”
Section: Existing Workmentioning
confidence: 99%
“…Correlation Heuristics. Correlation coefficients provide the existing association between variables in a dataset [DSouza and Velan S. 2020]. Examples of well-known correlations employed in the literature are Pearson, Spearman, and ANOVA.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In the exploratory data analysis, correlation measures can uncover, expose and show relationships between attributes of unlabeled data [Hoshen and Wolf 2018]. Analyzing the correlation between variables and their underlying interactions is essential for multivariable datasets [Zhang et al 2016] and has been the subject of study for decades now [DSouza and Velan S. 2020, Yang et al 2019, Kaieski et al 2016. This work aims to take advantage of correlation measures and visual tools to support the exploratory analysis and data understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic control is essential to prevent the spread of this outbreak from getting worse more widely. The literature suggests some official data sources issued by the government or agencies to be used to capture the evolutionary trajectory of COVID-19 [39], analyze infodemiology data for surveillance [40], formulate case patterns [41], and arranging appropriate quarantines activities [42]. Apart from official COVID-19 data, health insurance data can also be used to analyze the risk of being exposed to COVID-19.…”
Section: Healthcarementioning
confidence: 99%